Development and assessment of ketoconazole intravaginal thermosetting hydrogel formulations - Ramanah, Ashmita (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Imidazole compounds are commonly used as antifungal therapies and ketoconazole was the first broad spectrum orally active azole identified and registered. However, the risks of hepatotoxicity and drug interactions following systemic delivery and absorption of ketoconazole outweigh the therapeutic benefits and ketoconazole was therefore discontinued as first line systemic antifungal therapy in many countries. Although not yet banned in South Africa, the South African Medicine Formulary has ceased to recommend the use of ketoconazole for systemic treatment. Topical use of ketoconazole is, however, regarded as safe following extensive human use as low systemic absorption occurs following topical administration. Vulvo-vaginal candidiasis is a yeast infection that affects a large number of women, some of whom present with several infections annually. The topical treatment options for vulvo-vaginal candidiasis include the use of vaginal tablets, capsules, ovules and creams administered as a single dose or one to three times daily for three to fourteen days either alone or in combination with another dosage form depending on the regimen. Administration of the dose nightly is recommended for most vaginal creams and ovule formulation due to leakage and the uncomfortable feel of the dosage form if administered during the day. A thermosetting gel that remains in the vagina following administration and prolongs the release of ketoconazole from a once daily dose would be a useful addition to the arsenal for intra-vaginal antifungal therapy. Thermosetting gels would be more comfortable to administer as the gel would set in a form similar to naturally occurring mucous in the vagina and, if formulated with a low pH, irritation of the sensitive and fissured tissue would be minimised. A further benefit would be that once set the gel would loosely take on the anatomical shape of the vagina. A simple, precise, accurate, reproducible and sensitive stability-indicating reversed phase-high performance liquid chromatographic method using ultraviolet detection for the quantitation of ketoconazole was developed and validated. The method was specific and was applied to the determination of ketoconazole in commercial and experimental formulations in addition to samples from degradation studies and in vitro release testing. Product performance characteristics of commercial products were investigated with the goal to provide a strategy for the development of a novel intra vaginal gel in the shortest possible time. Characterisation of Xolegel®, Kez® shampoo and Ketazol® cream included an evaluation of pH, viscosity and assay, in addition to spectroscopic and thermal analysis, to identify ideal characteristics of topical products that could be used as targets during formulation development of the gel. An in vitro release method was developed and validated for precision and accuracy and the in vitro release profiles of commercial ketoconazole products were compared using analysis of variance, model dependent and independent approaches. Ketoconazole release data from test gel manufactured during formulation development were investigated to obtain information about the relationship between formulation content and drug release. Poloxamers marketed as Pluronic® and Lutrol® are synthetic non-ionic tri-block copolymers that consist of hydrophobic propylene oxide and hydrophilic polyethylene oxide blocks, which in solution interact to exhibit thermo-reversible behaviour. In situ forming hydrogels consisting of poloxamers, more specifically poloxamer 407, are activated following a temperature stimulus and undergo a sol to gel transition. This approach was used to produce a thermosetting vaginal gel that would exhibit a long residence time in the vagina with an associated enhancement of therapeutic efficacy. Ketoconazole- excipient compatibility was investigated during preformulation studies using spectroscopic and thermal analysis to enable the selection of excipients best suited for the production of a novel dosage form prior to formulation development activities. No obvious interactions between ketoconazole and excipient were observed and ketoconazole was found in an amorphous form when in combination with polysorbate 80 and poloxamers. A two-level factorial design was used to produce solvent systems with different amounts of polysorbate 80, citric acid and ethanol to identify a vehicle in which ketoconazole exhibited optimum solubility and at a pH that would be least irritating to the vaginal mucosa with a low content of excipients. The optimised vehicle consisted of 4% m/v citric acid, 1.5% v/v polysorbate 80 and 9.5% v/v ethanol made up to 50 g with citrate-phosphate buffer adjusted to pH 5.0, resulted in a vehicle of pH of 3.5 in which 71.41 mg of ketoconazole was dissolved per mL. A Central Composite Design was used to evaluate compositions for the modulation of viscosity of the thermosetting dosage form such that it was a liquid at 22 °C that rapidly formed a stiff gel when heated to 37 °C (intra-vaginal temperature) using different amounts of the poloxamer grades 407, 188 and 237. Thermosetting gels containing 2% m/v ketoconazole were manufactured using specifications generated using the Central Composite Design and the viscosity at 22 °C and 37 °C, solution to gel transition time, potency and ketoconazole release at 24, 48 and 72 hours investigated. Contour and three-dimensional response surface plots and mathematical relationships with target ranges set for responses were identified and with the aid of Central Composite Design the optimisation of a desirable thermosetting gel was achieved. The optimised composition included 16% m/v poloxamer 407, 10% m/v poloxamer 188 and 6% m/v poloxamer 237 in the gel that was used as the basis for further optimisation studies. The low ketoconazole release for ketoconazole observed indicated that the poloxamers had formed a gel matrix that sustained the release of ketoconazole and would therefore ensure that once daily administration of the gel was possible. The sol-gel transition test may be used as a simple and cheap alternative to viscosity testing for thermosetting formulations when expensive viscometers and rheometers are unavailable and was successfully used for this purpose.Ketoconazole is photolabile and is prone to degradation in aqueous solutions. The hydrophobic core of micelles formed in these dosage forms are believed to shield ketoconazole molecules and improve stability in aqueous solutions and acidic gels. The thermosetting gel optimised for poloxamer content was subjected to a further Central Composite Design in which sodium metabisulphite content and vehicle pH were investigated. The length of storage was used as a numeric variable and storage condition as a categoric variable at two levels to monitor the stability of the gels. The formulations were investigated at sample times of 0, 1, 2, 4 and 8 weeks at 5 °C, 25 °C and 40 °C. The use of a Central Composite Design facilitated an understanding of the interactions between input variables and their impact on the responses analysed including ketoconazole content, release at 24, 48 and 72 hours, gel pH and viscosity at 22 °C and 37 °C. Design of Experiments may be used as a rapid cost effective tool for an overall assessment of the stability of novel topical dosage forms. However, a more thorough assessment of stability may be required for product registration. Ketoconazole was found to be unstable in the acidic thermosetting gels despite the addition of antioxidant. The gels in liquid form at 5 °C and 25 °C have a low number of micelles for ketoconazole incorporation and therefore additional optimisation studies would be required to enhance the shelf-life of this product.
Keywords: Uncatalogued